The Manhattan weather in 1983 and 1984 - L. Dean Bark (Kansas Agricultural Experiment Station Research Reports, 1985)
The charts of the daily weather drawn by the KSU computer indicate what occurred in the past two years. The three smooth curves in each diagram represent the average conditions at Manhattan based on 70 years of records from the files of the Agricultural Experiment Stations Weather Data Library. The top two curves show the average maximum and minimum temperatures occurring throughout the year. They reach a low point in mid-January and climb to a peak in mid-July. The bottom smooth curve indicates the average accumulative precipitation during the year. Starting at zero on January 1, it increase during the year and ends at the average annual rainfall. It climbs steeply during the mid-year when precipitation is greatest on the average, and less steeply at the beginning and end of the year.
Keywords: Cattlemen& #x27; s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Weather